ANTI-INFLAMMATORY EFFECTS OF LOW PROTEIN DIET SUPPLEMENTED WITH KETO-AMINO ACID IN THE TREATMENT OF TYPE 2 DIABETIC NEPHROPATHY - Nan Chen; Yuanmeng Jin; Hong Ren; Jing Xu; Pingyan Shen; Xiaomin Huang (The Korean Society of Nephrology, 2012)
Recent clinical research strongly approves that low-protein diet supplemented with keto-amino acid can effectively delay progression of type 2 diabetic nephropathy (DN). Anti-inflammation is one of these effects, but the mechanism is still controversial. This study is designed to further explore roles of ketogenic diets in regulation of inflammation status of type 2 DN. Twenty-one patients with type 2 DN (mean age at 65.14±7.34 years), were followed-up for 52 weeks in this study. All patients were in CKD stages 3-4 with glomerular filtration rates 26-55 ml/min/1.73 m2 and were all on a low-protein diet containing 0.8 g protein/kg BW per day and 30-35 Kcal /kg BW per day. The diet was randomly supplemented with keto-amino acids at a dosage of 100 mg/kg BW per day in 10 patients, who were assigned into Group II. Other 11 patients were assigned into Group I. At the end of this study, related clinical data showed there was a significant increase in the serum level of TNF-α which could mediate inflammation systemically in Group I (from 230.25±54.34 to 332.11 pg/ml, P < 0.01), but non-significant increase in Group II (from 224.59±41.24 to 253.41±31.28 pg/ml, P>0.05). The level of CRP, which is produced in response to inflammation, rose greatly in Group I (from 7.5±1.07 to 20.4±3.72 ug/ml, P < 0.01), but decreased in Group II (from 8.2±3.07 to 3.9±1.22 ug/ml, P < 0.01). The level of adiponectin, an anti-inflammatory factor, was decreased in Group I (from 9.42±0.8 to 7.64±1.4 μg/ml, P< 0.05), but showed slight increase in Group II (9.04±0.9 versus 10.47±1.2= μg/ml, P>0.05). Nutritional markers including serum albumin, hemoglobin and basal metabolic index showed no malnutrition happened during the follow-up period. In conclusion, low-protein diet supplemented with keto-amino acids contribute to ameliorate inflammation in the progression of type 2 diabetic nephropathy through regulating inflammatory factors production, including TNF-α, CRP and adiponectin.